2021
DOI: 10.1186/s12883-021-02413-3
|View full text |Cite
|
Sign up to set email alerts
|

Higher fasting C-peptide is associated with post-stroke depression: a multicenter prospective cohort study

Abstract: Background Fasting C-peptide (FCP) has been shown to play an important role in the pathophysiology of mood disorders including depression and schizophrenia, but it is unknown whether it also predicts post-stroke depression (PSD). This study examined the association between FCP and PSD at 6 months after acute ischemic-stroke onset among Chinese subjects. Methods A total of 656 stroke patients were consecutively recruited from three hospitals of Wuha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
2
1
0
1
Order By: Relevance
“…A total of 39.7% of acute ischemic stroke patients were diagnosed as PSD at 3 months in this study, which is similar to the incidence reported in previous studies. 31 , 32 Our results suggested that female and those who are physically inactive are at higher risk for PSD, which were consistent with previous studies. 33 , 34 Our results also demonstrated that patients with PSD had significantly increased stroke severity and worse functional outcome, which was the same as other studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A total of 39.7% of acute ischemic stroke patients were diagnosed as PSD at 3 months in this study, which is similar to the incidence reported in previous studies. 31 , 32 Our results suggested that female and those who are physically inactive are at higher risk for PSD, which were consistent with previous studies. 33 , 34 Our results also demonstrated that patients with PSD had significantly increased stroke severity and worse functional outcome, which was the same as other studies.…”
Section: Discussionsupporting
confidence: 92%
“…The underlying mechanism might be that high levels of fasting C-peptide reflect insulin resistance and disrupted glucose metabolism, which contributes to depression. 31 Furthermore, previous studies have confirmed that neutrophil count 25 as well as IL.6 37 were involved in the development of PSD and our study came to the same conclusion.…”
Section: Discussionsupporting
confidence: 87%
“…Имеются все основания полагать, что повышение уровня С-пептида в крови ассоциировано с повышением содержания С-пептида в мозге, тем более что рецепторный механизм в транспорте С-пептида через ГЭБ, который мог бы меняться в условиях гипер-С-пептидемии, не показан. Имеются данные о том, что повышенные уровни С-пептида при СД2 и ожирении могут негативно влиять на функционирование микрососудов головного мозга и быть причиной ряда функциональных расстройств нервной и сердечно-сосудистой систем (Alves et al 2019;Chen et al 2021;Wang et al 2021). В основе этого лежит доказанное тромболитическое действие С-пептида при его высоких концентрациях, а также стимулирующее влияние С-пептида на рост гладкомышечных клеток сосудов, приводящее к атеросклеротическим изменениям (Alves et al 2019).…”
Section: Discussionunclassified
“…All tests were two-sided, and a P -value of 0.05 was defined to indicate statistical significance. Subsequently, variables with p < 0.05 were entered into a multivariable logistic regression model in a backward stepwise method ( 21 ). The above-mentioned analysis process was realized by Statistical Program for Social Sciences (SPSS) statistical software (version 25, Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%